1994
DOI: 10.1172/jci117585
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase is expressed in cultured human bronchiolar epithelium.

Abstract: IntroductionNitric oxide (NO) is an important mediator of physiologic and inflammatory processes in the lung. (2), and endothelium-derived NO relaxes tracheal smooth muscle in vitro (3). In addition, endogenous NO gas is present in the exhaled air of animals and humans (4), and endogenous nitrogen oxides and bronchodilator S-nitrosothiols have been demonstrated in human airways (5). Furthermore, air or helium embolization of the rabbit pulmonary artery does not alter exhaled NO concentrations, suggesting that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
115
1
6

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(131 citation statements)
references
References 44 publications
9
115
1
6
Order By: Relevance
“…This was anticipated for the constitutive isoforms bNOS and eNOS (Asano et al, 1994;Kobzik et al, 1993;Shaul et al, 1994;Steudel et al, 1999), although an entire profile of cellular localization of both isoforms in lung tissue has so far not been shown. A recent study reported eNOS expression in epithelial cells, endothelial cells, and VSMC in normal rat lung tissue, which corresponds well with the data presented in this study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This was anticipated for the constitutive isoforms bNOS and eNOS (Asano et al, 1994;Kobzik et al, 1993;Shaul et al, 1994;Steudel et al, 1999), although an entire profile of cellular localization of both isoforms in lung tissue has so far not been shown. A recent study reported eNOS expression in epithelial cells, endothelial cells, and VSMC in normal rat lung tissue, which corresponds well with the data presented in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Three isoenzymes of NOS have been described Moncada and Higgs, 1993): the neuronal isoform bNOS (NOS-1) and an endothelial isoform eNOS (NOS-3) as constitutive isoenzymes, and a mitogeninducible isoform iNOS (NOS-2). Cellular expression of bNOS and eNOS in different cell types of normal lung tissue and pulmonary cell cultures has been reported earlier (Kobzik et al, 1993;Shaul et al, 1994;Sherman et al, 1999). Cellular expression of iNOS in the lung parenchyma has so far only been observed after experimental endotoxin stimulation or in sections from patients suffering from inflammatory lung disease (Kobzik et al, 1993;Robbins et al, 1994;Tracey et al, 1994).…”
mentioning
confidence: 87%
“…Our observation that TLR7's effects occurs within minutes in vitro and within seconds in vivo is consistent with neuronal nitric oxide synthase's kinetics. Although the nitric oxide synthase inhibitors used in these experiments were not specific for a particular nitric oxide synthase isozyme, endothelial nitric oxide synthase is located in airway epithelium (37), which is not involved in TLR7's effect, whereas inducible nitric oxide synthase is transcriptionally ; Figure 4. Toll-like receptor (TLR) 7 is expressed on a subpopulation of human and murine airway nerves but not airway smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…As três isoformas de NOS estão presentes em vias aéreas (Robbins et al,1994;Shaul, 1994;FloraFilho e Zilberstein, 2000).…”
Section: Efeitos Fisiológicos Nos Nosunclassified
“…O NO é expresso constitutivamente no epitélio bronquial (Shaul et al, 1994) e em células epiteliais alveolares do tipo II humanas (Pechkovsky et al, 2002) é encontrado também vasos sanguíneos pulmonares (Shaul et al, 2002) e em todos tipos de artérias, particularmente na artéria radial. (Gaudino et al, 2003).…”
Section: Efeitos Fisiológicos Nos Nosunclassified